Genetic modification of a baculovirus vector for increased expression in insect cells. - Hitchman, R; Possee, R; Crombie, A; Chambers, A; Ho, K; Siaterli, E; Lissina, O; Sternard, H; Novy, R; Loomis, K; Bird, L; Owens, R; et al. (2010)
Generating large amounts of recombinant protein in transgenic animals is often challenging and has a number of drawbacks compared to cell culture systems. The baculovirus expression vector system (BEVS) uses virus-infected insect cells to produce recombinant proteins to high levels, and these are usually processed in a similar way to the native protein. Interestingly, since the development of the BEVS, the virus most often used (Autographa californica multi-nucleopolyhedovirus; AcMNPV) has been little altered genetically from its wild-type parental virus. In this study, we modified the AcMNPV genome in an attempt to improve recombinant protein yield, by deleting genes that are non-essential in cell culture. We deleted the p26, p10 and p74 genes from the virus genome, replacing them with an antibiotic selection cassette, allowing us to isolate recombinants. We screened and identified recombinant viruses by restriction enzyme analysis, PCR and Western blot. Cell viability analysis showed that the deletions did not improve the viability of infected cells, compared to non-deletion viruses. However, expression studies showed that recombinant protein levels for the deletion viruses were significantly higher than the expression levels of non-deletion viruses. These results confirm that there is still great potential for improving the BEVS, further increasing recombinant protein expression yields and stability in insect cells.